Experimental and multiscale analysis of volume fraction effects in tensile properties of recycled PLA-PDA/kenaf fiber 3D printing filament composites - Hamat, Sanusi; Ishak, M.R.; Salit @ Sinon, Mohd Sapuan; Yidris, N.; Hussin, M.S.; Showkat Ali, S.A.; Ibrahim, M. (Taylor and Francis, 2024)
Polylactic acid, a biodegradable thermoplastic derived from renewable sources, has notable environmental advantages and versatile properties. However, recycled PLA often experiences reduced mechanical strength and altered chemical composition due to the recycling process, limiting its suitability for 3D printing filament applications. Recognizing the inherent limitations of recycled PLA (rPLA), this research employs a unique method of coating rPLA with dopamine (DA) and reinforcing it with kenaf fibers (KF) at various weight fractions, introducing a novel multiscale modeling approach to address the challenges of interfacial bonding and tensile performance in recycled polymers. The methodology integrates experimental single filament tensile testing with multiscale finite element modeling to accurately predict the composite’s mechanical behavior across different scales. The findings reveal that a 5% kenaf fiber weight/volume fraction provides the optimal balance between tensile strength, stiffness, and toughness, achieving a significant 49.3% improvement over the unreinforced rPLA. However, increasing the kenaf fiber content beyond 5% leads to a decline in mechanical properties, attributed to higher fiber agglomeration and suboptimal fiber-matrix interactions. The novelty of this research lies in its combined use of PDA coating, natural kenaf fiber reinforcement, and advanced multiscale modeling to enhance and predict the performance of rPLA-PDA/kenaf composites, paving the way for sustainable, high-performance materials in 3D printing applications.